(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The modern progressive movement that emerged in Turkestan in the late 19th - early 20th centuries occupies an important place in the centuries-old history of the Uzbek people. Mahmudhoja Behbudi, Munavvarqori Abdurashidkhanov, Ubaydulla Khojaev, Obidjon Mahmudov, Fitrat, Cholpon, Saidnosir Mirjalilov and others took the first step towards uniting the local people under the banner of national independence, seizing power and establishing a national Uzbek state.